Unusual Renal and Colonic Mass: Description of a Rare Case - Khare, Manika; Ahuja, Arvind; Bhardwaj, Minakshi; Khattar, Nikhil (Indian Journal of Medical and Paediatric Oncology, 2019)
Seminoma is a germ cell tumor which accounts for approximately 40% of all germ cell tumors. Testicular seminoma is usually localized to the testis, and in 25% of cases, lymph node metastasis is seen. However, rarely, it can metastasize to visceras. We report a rare case of metastatic seminoma in a 40-year-old male who presented with renal and intestinal mass 2 years after orchidectomy.
Keywords: Intestinal; metastasis; renal; seminoma; testis